Integration of Statistical Process Control (SPC) and Engineering Process Control (EPC) for quality improvement: article / Fatin Fazliyana Mohd Latif, Sherif Abdulbari Ali and Nur Amalina Hamzah - Mohd Latif, Fatin Fazliyana; Abdulbari Ali, Sherif; Hamzah, Nur Amalina (2019)
SPC and EPC play a different role in manufacturing process quality control. Generally, SPC used to remove assignable causes from the process, while EPC used to keep the process output on the set point by reducing process variability. Both method can identify the effect of process that cause by irregularity and variability in the process that result of errors and poor quality. Previous research was improved the product quality by using EPC independently. They have found that using EPC alone is unable to cope with assignable cause variation. Therefore, using the SPC and EPC integrated control can better ensure the quality of the product. In this research, the methodology used continuous stirred tank reactor model process from past literature was performed by using Simulink Matlab for the simulation and then, continued with Process Capability Six pack in Minitab for further statistical report analysis, where the system was implemented in a chemical process together with existent PID feedback controllers for non-isothermal continuous stirred tank reactor (CSTR). The experimental result clearly shows that process variability was reduced about 76.54%. It is concluded that integrated approach has better way to achieve continuously quality improvement than that using EPC alone.